PRELIMINARY STUDY ON PLASTICINE AS A SUBSTITUTE COHESIVE MATERIAL FOR GEOTECHNICAL PHYSICAL SOIL MODELING - Purwana, Yusep Muslih; Setiawan, Bambang; Danajaya, Raden Harya; Bagaskara, Brilliant (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2021)
Plasticine is an artificial material made from solids such as gypsum, lime, mixed with petroleum jelly or micro wax and acid fat. The properties of plasticine are likely similar to natural clay and is influenced by oil content. The information about mechanical properties of plasticine is still very rare, and as such the study on it is riquired and must be conducted intensively. The preliminary laboratory study has been conducted to understand the behaviour of plasticines. Microwax and petroleum jelly based plasticines were utilised with the variation of oil content, whereas kaolin clay with the variation of water content is utilised as a reference material. The study is focusing on the stress-strain behaviour for both microwax and petroleum jelly based plasticines compared to the stress-strain behaviour of kaolin clay. This paper reports the result of preliminary investigation regarding the use of plasticine as an alternative artificial material for substitution of clay in soil modeling. Some engineering properties from unconfined compression strength (UCS) test and hand penetrometer are shown. The result indicates that the stress-strain behaviour of plasticine resembles the stress-strain behaviour of kaolin clay. The plasticine is suitable as a substitute cohesive material and it has a potential to be utilised for geotechnical material modelling in the future.